The Development of Plant Ecophysiology Research Based Learning Materials on Photosynthesis Subject - Sri Wulandari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Research development of teaching materials photosynthesis on the subject Ecophysiology plant based research aims to: (1) for the type and ratio of organic matter to the soil mixture former bauxite mine is best to plant photosynthesis rubber clone PB 260. (2) Enriching teaching materials in the form of modules Ecophysiology plant based experimental research. Stage of research include; (1) Experiment with 3 treatment ratio (w / w): control, (1: 1), (1: 2) to design completely randomized design. Data analysis by ANOVA and Duncan's Multiple Range Test Test. (2) Development of teaching materials in the form of plant ecophysiology module using ADDIE development model (Dick and Carey). The results showed a mixture of organic matter to the soil manure former bauxite mine is better than chicken manure with a mixture ratio of 1: 2. Modules developed from the results of the experiment show valid with an average of 3.32. The module has a good practical in terms of ease of use, time used to study the module, the material is quite clear from the data presented research results in the form of drawings (graphs) and tables. Student learning outcomes everything including the excellent category with a range of values 81 - 85. The module is useful to increase knowledge of students in special ecophysiology plant and botany in general.Keywords: teaching materials, photosynthesis, soil former bauxite mine